“DEXA” as a tool for body composition prediction, and effects of methionine sources on broilers in the starter, grower, and finisher phases - Aguiar, Gustavo Augusto Carvalho Costacurta de (2024)
Three trials were conducted to evaluate two sources of methionine supplementation in a basal diet in starter, grower, and finisher broilers, respectively. Each trial used 1,820 Cobb500 male, and was performed in a completely randomized design (2 sources × 6 levels), 7 replicates and a common basal diet deficient in methionine. The methionine sources were liquid Met hydroxy-analogue (HMTBA) and DL- methionine (DLM) included in equimolar basis to obtain the levels of 0.04, 0.08, 0.13, 0.2, 0.3, and 0.4% for starter; 0.04, 0.08, 0.12, 0.17, 0.25, and 0.33% for grower and 0.04, 0.08, 0.12, 0.17, 0.24, and 0.32% for finisher. For all trials, growth performance and body chemical composition were evaluated, while carcass and commercial cuts yields were evaluated only in grower and finisher phases. Three chapters were created with the results obtained in all trials. The first, comprehends the development and validation of linear regression equations for body composition prediction using Dual-energy X-ray absorptiometry (DEXA). As results, prediction equations for weight, fat mass, ash mass, lean mass, water mass and protein mass were validated indicating that DEXA is an alternative to measure the body composition of broilers in a non-invasive and non-destructive manner. The second chapter is about the effect of increasing SID Met+Cys:Lys ratios on growth, carcass, and meat yield responses of broilers, and estimate the optimal ratio for starter, grower, and finisher phases. The SID Met+Cys:Lys ratios used were different for starter (53, 57, 61, 67, 75 and 83%), grower (54, 58, 62, 67, 75 and 83%), and finisher (54, 58, 63, 68, 75 and 83%). Results suggest that as birds mature, Met+Cys requirements initially increase, and then slightly decrease. Met supplementation resulted in broiler carcasses with lower fat, but higher protein and mineral. For starter, optimal ratios were 58% for final body weight (FBW) and average daily weight gain (ADWG), 71% for feed conversion ratio (FCR), and 69% for average daily protein deposition. For grower, the ratios were 76% for FBW and ADWG, 81% for FCR, 70% for average daily ash deposition, and 63% for carcass weight (CW). For finisher, requirements were 77% for FCR, 61% for CW,and 58% for carcass yield. Formulating diets to meet growth performance requirements will also attend the carcass composition and meat yields. The third chapter includes the effect of different Met sources on broilers, and the relative bioavailability value (RBV) in equimolar basis of HMTBA to DLM estimated with multi- exponential model. Birds fed DLM presented better results for growth performance in grower and finisher broilers, while the starter birds presented higher protein and ash deposition in their body. The RBV for starter is 99% for growth parameters. In grower is 79% for FBW, 80% for ADWG, 76% for FCR, 66% for CW, 236% for carcass yield, 70% for breast meat yield, and 128% for thigh yield. And for finisher is 79% for FCR, 77% for CW, and 65% for thigh yield. Therefore, DLM provides a better body composition quality for young birds, and the replacement of DLM with HMTBA should consider the animal's growth phase for choosing appropriate RBV. Keywords: amino acids; requirement; bioefficacy; methionine hydroxy-analogue; body analysis.